Nanotechnology in Osteogenesis and Inflammation Management: Metal–Organic Frameworks, Metal Complexes, and Biomaterials for Bone Restoration - Bogdan Huzum; Ionut Iulian Lungu; Ovidiu Alexa; Paul Dan Sirbu; Viorel Dan Cionca; Andreia Corciova; Andreea Lungu; Monica Hancianu; Ionela Lacramioara Serban; Oana Cioanca (Biomedicines)
A varied family of polyphenolic chemicals, flavonoids, are becoming more and more important in bone tissue engineering because of their osteogenic, anti-inflammatory, and antioxidant effects. Recent developments incorporating flavonoids into different biomaterial platforms to improve bone regeneration are emphasized in this study. Osteocalcin (OCN) expression was 2.1-fold greater in scaffolds loaded with flavonoids—such as those made of polycaprolactone (PCL)—greatly increasing human mesenchymal stem cell (hMSC) proliferation and mineralization. Comparably, a threefold increase in calcium deposition indicates increased mineralization when hydroxyapatite (HA) was functionalized with flavonoids such as quercetin. These HA scaffolds with flavonoids also showed a 45% decrease in osteoclast activity, therefore promoting balanced bone remodeling. Concurrent with flavonoids like EGCG and quercetin, chitosan-based scaffolds encouraged osteogenic differentiation with increases in osteogenic markers like osteopontin (OPN) and alkaline phosphatase (ALP) expression by up to 82%. These scaffolds also showed 82% bone defect repair after six weeks in vivo, suggesting their promise in rapid bone regeneration. With an increase of up to 32% in the bone volume-to-total volume ratio (BV/TV) and 28% greater bone–implant contact (BIC), flavonoid coatings on titanium implants enhanced osteointegration in implantology. Displaying successful osteogenesis and immunomodulation, the addition of flavonoids into metal–organic frameworks (MOFs) and injectable hydrogels demonstrated a 72% increase in new bone formation in vivo. Though further research is required to confirm long-term clinical effectiveness, these findings show the great promise of flavonoid-functionalized biomaterials in bone regeneration.